Self-Assembly of Pluronic F127Silica Spherical Core–Shell Nanoparticles in Cubic Close-Packed Structures - Kerkhofs, Stef; Willhammar, Tom; Van Den Noortgate, Heleen; Kirschhock, Christine E. A; Breynaert, Eric; Van Tendeloo, Gustaaf; Bals, Sara; Martens, Johan A (Chemistry of materials, 2015)
A new ordered mesoporous silica material (COK-19) with cubic symmetry is synthesized by silicate polycondensation in a citric acid/citrate buffered micellar solution of Pluronic F127 triblock copolymer near neutral pH. SAXS, nitrogen adsorption, TEM, and electron tomography reveal the final material has a cubic close packed symmetry (Fm3̅m) with isolated spherical mesopores interconnected through micropores. Heating of the synthesis medium from room temperature to 70 °C results in a mesopore size increase from 7.0 to 11.2 nm. Stepwise addition of the silicate source allows isolation of a sequence of intermediates that upon characterization with small-angle X-ray scattering uncovers the formation process via formation and aggregation of individual silica-covered Pluronic micelles.